The Influence of the Principal's Leadership Style on Teacher Performance at Madrasah Aliyah Suka Negeri, South Bengkulu Regency - Junaidi Junaidi; Oni Yulianti; Nia Indriasari (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine the effect of the principal's leadership style on teacher performance at Madrasah Aliyah Suka Negeri, South Bengkulu Regency. The sample in this study were 30 teachers who teach at Madrasah Aliyah Suka Negeri, South Bengkulu Regency. Collecting data using a questionnaire and the analytical method used is simple linear regression analysis,determination test and hypothesis testing.Based on the results of the study, it shows a simple linear regression equation,namely Y = 16.211 + 0.624X with a positive regression direction meaning that if the principal's leadership style increases, the performance of teachers at Madrasah Aliyah Suka Negeri, South Bengkulu Regency will also increase. The principal's leadership style has a significant effect on teacher performance at Madrasah Aliyah Suka Negeri, South Bengkulu Regency, because the significant value of 0.001 is smaller than 0.05. This means that the higher the leadership style of the Principal at Madrasah Aliyah Suka Negeri, South Bengkulu Regency, the teacher's performance will also increase. The coefficient of determination of R square is 0.352. This means that the principal's leadership style has an influence on teacher performance by 35.2% while the rest (100-35.2% = 64.8%) is influenced by other causal factors not examined in this study.